Forest 404: Using a BBC drama series to explore the impact of nature's changing soundscapes on human wellbeing and behavior. (May 2022) - Smalley, Alexander J.; White, Mathew P.; Ripley, Rebecca; Atack, Timothy X; Lomas, Eliza; Sharples, Mike; Coates, Peter A.; Groom, Nick; Grand, Ann; Heneberry, Ailish; Fleming, Lora E.; Depledge, Michael H.
Highlights: A novel and transdisciplinary eco-thriller podcast series was produced by the BBC. An integrated experiment explored appraisals of changing natural soundscapes. Participants responded differently to soundscapes with and without audible wildlife. Lived experience moderated both restorative potential and preservation motivation. Perceived therapeutic qualities partly mediated desires to preserve natural sounds. Abstract: Extensive ecosystem degradation and increasing urbanization are altering human relationships with nature. To explore these trends, we created a transdisciplinary, narrative-led podcast series produced by the BBC, called Forest 404 . The series explored the implications of a world without nature. An online experimental component mobilized audience participation (n = 7, 596) to assess responses to natural soundscapes with and without abiotic, biotic, and poetic elements across five biomes. Conditions featuring the sounds of wildlife, such as bird song, were perceived to be more psychologically restorative than those without. Participants' personal lived experiences were strongly related to these outcomes; those who had memories triggered by the sounds were more likely to find them psychologically restorative and exhibited a greater motivation to preserve them. Moreover, the effects of both soundscape composition and memories on preservation behavior were partially mediated by restorative potential; respondents were more likely to want to protect the sounds they heard if they thought they might offer therapeutic outcomes. Our findings highlight the value of art-science collaborations and demonstrate how maintaining contact with the natural world can promote wellbeing and foster behaviors that protect planetary health.